Astragaloside IV alleviates 1-deoxysphinganine-induced mitochondrial dysfunction during the progression of chronic kidney disease through p62-Nrf2 antioxidant pathway - Gui, Ting; Chen, Qingfa; Li, Jiangsong; Lu, Ke; Li, Chen; Xu, Bin; Chen, Yang; Men, Jingwen; Kullak-Ublick, Gerd A.; Wang, Weihua; Gai, Zhibo (Frontiers in Pharmacology, 2023)
Chronic kidney disease (CKD) can lead to significant elevation of 1-deoxysphingolipids (1-deoxySL). The increase of 1-deoxySL in turn can result in mitochondrial damage and oxidative stress, which can cause further progression of CKD. This study assessed the therapeutic effect of Astragaloside IV (AST) against 1-deoxySL-induced cytotoxicity in vitro and in rats with CKD. HK-2 cells were exposed to 1-deoxysphinganine (1-deoxySA) or 1-deoxySA+AST. 1-deoxySA-induced mitochondrial dysfunction and oxidative stress were evaluated by immunostaining, real-time PCR, oxidative stress sensor, and transmission electron microscopy. The potential effects of AST on kidney damage were evaluated in a rat 5/6 nephrectomy (5/6 Nx) model of CKD. The findings of in vitro experiments showed that 1-deoxySA induced mitochondrial damage, oxidative stress, and apoptosis. AST markedly reduced the level of mitochondrial reactive oxygen species, lowered apoptosis, and improved mitochondrial function. In addition, exposure to AST significantly induced the phosphorylation of p62 and the nuclear translocation of Nrf2 as well as its downstream anti-oxidant genes. p62 knock-down fully abolished Nrf2 nuclear translocation in cells after AST treatment. However, p62 knock-down did not affect TBHQ-induced Nrf2 nuclear translocation, indicating that AST can ameliorate 1-deoxySA-induced oxidative stress through modulation of p62 phosphorylation and Nrf2 nuclear translocation. The findings indicate that AST can activate Nrf2 antioxidant pathway in a p62 dependent manner. The anti-oxidative stress effect and the further mitochondrial protective effect of AST represent a promising therapeutic strategy for the progression of CKD.